Acupuncture-related therapy for cancer-related insomnia: An overview of systematic reviews and meta-analysis - Zining Guo; Yuting Wang; Wenhao Liu; Haifu Huang; Xiaorong Tang; Zhennan Wu; Liming Lu; Baochao Fan; Shaoyang Cui; Nenggui Xu (Elsevier, 2024)
Background: The number of systematic reviews and meta-analyses (SRs/MAs) on acupuncture therapy for CRI is increasing; however, the credibility of the evidence remains unclear with controversial results, necessitating a comprehensive evaluation. Objective: We aimed to critically assess the evidence in SRs/MAs regarding the effectiveness of acupuncture therapy for CRI from various aspects and conduct an exploratory analysis to identify potential issues. Method: Two reviewers conducted comprehensive searches in eight databases. SRs/MAs of randomized controlled trials are included. After screening according to inclusion and exclusion criteria, two reviewers extracted data from eligible SRs/MAs and conducted a detailed assessment of methodological quality, risk of bias, and quality of evidence using AMSTAR-2, ROBIS, and GRADE tools. Meanwhile, we calculated the Corrected Covered Area (CCA) leveraging the GROOVE tool. After manually excluding duplicate studies, we assess the risk of bias of primary studies extracted from SRs/MAs and conducted exploratory meta-analysis. Result: The comprehensive analysis included 10 SRs/MAs. The AMSRAT-2 results indicate significant methodological flaws in SRs/MAs, with the main issues focusing on the lack of provision of exclusion checklist for the studies. Furthermore, over half of the SRs/MAs have a high risk of bias due to incomplete retrieval and failure to follow the protocol. Most SRs/MAs demonstrated considerable completeness in reporting quality. Notably, the overall level of evidence is low. High overlap indicates redundant SRs/MAs. Exploratory analysis suggests that acupuncture therapy may be effective for CRI; however, with a high risk of bias, caution is needed in interpreting the results. Sensitivity analysis results are stable, and the funnel plot indicates no publication bias. Most SRs/MAs acknowledge the safety of acupuncture. Conclusion: Currently, the credibility of acupuncture therapy for treating CRI is low and improvements are needed in methodology, risk of bias, and quality of reporting. Acupuncture therapy shows potential but lacks sufficient support; high-level evidence is warranted to elucidate the effectiveness of acupuncture in treating CRI.